THE STUDY OF SEMANTIC FIELDS IN COMPARATIVE LINGUISTICS - Amanov Alisher Kahramonovich (Western European Studies, 2025)
This article analyzes the concept of semantic fields in comparative linguistics and its significance within the discipline. Semantic fields represent systematic groupings that form the lexical structure and domains of meaning in language. In this field of linguistics, semantic fields play an important role in identifying both differences and similarities between languages. The article provides detailed information on semantic fields, their connection with language and culture, as well as various methodological approaches accepted by linguists, such as semantic mapping, componential analysis, prototype theory, and cognitive analysis. Through comparative analysis, the unique characteristics and cultural contexts of languages are thoroughly examined.
Keywords: comparative linguistics; semantic field; lexical units